Synthesis of multifunctional CuFe2O4–reduced graphene oxide nanocomposite: an efficient magnetically separable catalyst as well as high performance supercapacitor and first-principles calculations of its electronic structures. Issue 49 (3rd August 2018) - Chandel, Madhurya; Moitra, Debabrata; Makkar, Priyanka; Sinha, Harshit; Hora, Harshdeep Singh; Ghosh, Narendra Nath
Abstract : Here, we report an ' in situ ' co-precipitation reduction based synthetic methodology to prepare CuFe2 O4 nanoparticle–reduced graphene oxide (CuFe2 O4 –RGO) nanocomposites. Abstract : Here, we report an ' in situ ' co-precipitation reduction based synthetic methodology to prepare CuFe2 O4 nanoparticle–reduced graphene oxide (CuFe2 O4 –RGO) nanocomposites. First principles calculations based on Density Functional Theory (DFT) were performed to obtain the electronic structures and properties of CuFe2 O4, graphene and CuFe2 O4 –graphene composites, and to understand the interfacial interaction between CuFe2 O4 and graphene in the composite. The synergistic effect, which resulted from the combination of the unique properties of RGO and CuFe2 O4 nanoparticles, was exploited to design a magnetically separable catalyst and high performance supercapacitor. It has been demonstrated that the incorporation of RGO in the composite enhanced its catalytic properties as well as supercapacitance performance compared with pure CuFe2 O4 . The nanocomposite with 96 wt% CuFe2 O4 and 4 wt% RGO (96CuFe2 O4 –4RGO) exhibited high catalytic efficiency towards (i) reduction of 4-nitrophenol to 4-aminophenol, and (ii) epoxidation of styrene to styrene oxide. For both of these reactions, the catalytic efficiency of 96CuFe2 O4 –4RGO was significantly higher than that of pure CuFe2 O4 . The easy magnetic separation of 96CuFe2 O4 –4RGO from the reaction mixture and good reusability of the recovered catalyst also showed here. 96CuFe2 O4 –4RGO also demonstrated better supercapacitance performance than pure CuFe2 O4 . 96CuFe2 O4 –4RGO showed specific capacitance of 797 F g −1 at a current density of 2 A g −1, along with ∼92% retention for up to 2000 cycles. To the best of our knowledge, this is the first investigation on the catalytic properties of CuFe2 O4 –RGO towards the reduction of 4-nitrophenol and the epoxidation reaction, and DFT calculations on the CuFe2 O4 –graphene composite have been reported.